2019
DOI: 10.1007/s11079-019-09560-8
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of External Imbalances in the European Periphery

Abstract: The issue of external imbalances has become a key concern in the global economy, gaining particular prominence also inside Europe, following the Eurozone crisis. Comparatively, however, evidence for the European periphery is much less developed. In this study we investigate the sustainability of external imbalances in 15 countries from the EU's so-called eastern and super-periphery across a range of sustainability tests. We find that external imbalances are on the whole large and, despite some significant adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Evaluating the current account requires the use of appropriate equilibrium values or norms, which also aid in anticipating future adjustment needs and potential dynamics of economic fundamentals (Comunale, 2015). Several studies, including those by Shfferin and Woo (1990), Obstfeld and Rogoff (1995), Otto and Voss (1995), Bergin (2006) Monastiriotis and Tunali (2020), have identified key determinants of current account deficits. However, none of these studies have explored the relationship between foreign capital inflow and the determinants of current account deficits in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the current account requires the use of appropriate equilibrium values or norms, which also aid in anticipating future adjustment needs and potential dynamics of economic fundamentals (Comunale, 2015). Several studies, including those by Shfferin and Woo (1990), Obstfeld and Rogoff (1995), Otto and Voss (1995), Bergin (2006) Monastiriotis and Tunali (2020), have identified key determinants of current account deficits. However, none of these studies have explored the relationship between foreign capital inflow and the determinants of current account deficits in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through an extensive review of the literature, it becomes evident that the current account deficit is a subject of interest among researchers and policymakers. Various studies (Comunale, 2015 Monastiriotis and Tunali, 2020) have identified key factors influencing the current account deficit. However, none of these studies have explored the connection between foreign capital inflow and the determination of the current account deficit specifically in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%